Integrated treatment of olive mill wastewater (OMW) by the combination of Fenton's reaction and anaerobic treatment - El-Gohary, F.A.; Badawy, M.I.; El-Khateeb, M.A.; El-Kalliny, A.S. (Journal of hazardous materials, 2009)
The use of an integrated treatment scheme consisting of wet hydrogen peroxide catalytic oxidation (WHPCO) followed by two-stage upflow anaerobic sludge blanket (UASB) reactor (10 l each) for the treatment of olive mill wastewater was the subject of this study. The diluted wastewater (1:1) was pre-treated using Fenton's reaction. Optimum operating conditions namely, pH, H 2O 2 dose, Fe +2, COD:H 2O 2 ratio and Fe +2:H 2O 2 ratio were determined. The UASB reactor was fed continuously with the pre-treated wastewater. The hydraulic retention time was kept constant at 48 h (24 h for each stage). The conventional parameters such as COD, BOD, TOC, TKN, TP, TSS, oil and grease, and total phenols were determined. The concentrations of polyphenolic compounds in raw wastewater and effluents of each treatment step were measured using HPLC. The results indicated a good quality final effluent. Residual concentrations of individual organic compounds ranged from 0.432 mg l −1 for ρ-hydroxy-benzaldhyde to 3.273 mg l −1 for cinnamic acid.